Morphology of mouse subplate cells with identified projection targets changes with age. - Hoerder-Suabedissen, A; Molnár, Z (2012)
During embryonic and early postnatal development subplate neurons integrate into the developing intra- and extracortical circuitry in a dynamic fashion. They extend long-range projections to adjacent cortical regions, the contralateral hemisphere through the corpus callosum, and to subcortical structures through the internal capsule. Here we studied the developmental changes of the somatodendritic morphology of subplate neurons with specified projection target in the mouse. To do so we used carbocyanine dye tracing from the callosum, the internal capsule, or the primary somatosensory cortex. The morphology of subplate cells with projections to any of these targets is very diverse and includes pyramidal, multipolar, and neurogliaform cells. Here we demonstrate that a subpopulation of subplate cells in the mouse cortex undergoes significant changes in somatodendritic morphology during the critical period for experimental modification of the cytoarchitectonic development of the barrel cortex. Between P2 and P7 the mean maximal extent of the primary dendrite decreases significantly for subplate cells with an axon projecting through the internal capsule. Moreover, at P2 some subplate cells extend a primary dendrite to the marginal zone, whereas all dendrites of P7 subplate cells end in or below layer 4. Additionally, by tracing connections from multiple targets with different carbocyanine dyes we identified subplate cells with multiple long-range projections.